1996
DOI: 10.1103/physrevlett.77.1012
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of theppdπ+Cross Section and Analyzing

Abstract: Differential cross sections and analyzing powers for the pp ! dp 1 reaction have been measured to within T cm p 85 keV of threshold. The S-wave strength is extracted and found to be ϳ13% larger than that determined from recent measurements of np ! dp 0 . Both the analyzing power and the anisotropy in the angular distribution show the expected energy dependence and these data are used to obtain values for the two contributing P-wave amplitudes. [S0031-9007(96)00564-9] PACS numbers: 13.75. Cs, 24.70. + s, 25.40.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 17 publications
4
44
0
Order By: Relevance
“…We systematically found larger cross sections than given in [1], [3]. Since the results we deduced from the data for the concurring charged π-producing reactions agreed nicely with the published values [7], [10], [11], whereas the cross sections for π 0 -production remained high, we decided to perform a second experiment to clarify that matter.…”
Section: Introductionsupporting
confidence: 45%
See 2 more Smart Citations
“…We systematically found larger cross sections than given in [1], [3]. Since the results we deduced from the data for the concurring charged π-producing reactions agreed nicely with the published values [7], [10], [11], whereas the cross sections for π 0 -production remained high, we decided to perform a second experiment to clarify that matter.…”
Section: Introductionsupporting
confidence: 45%
“…For comparison, angular distributions as well as analyzing powers extracted from a study of the π + -producing reactions show clear evidence for the presence of Sp, and hence l = 1 contributions at energies as low as 2 MeV above threshold [10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pion reactions with few-nucleon systems [17][18][19][20][21]. Note that the green diamond and the blue triangle correspond to the most resent measurements from pionic deuterium atom [20,21] at η = 0.…”
Section: Pos(cd09)030mentioning
confidence: 99%
“…In recent studies it was found that within 10-20 MeV of threshold, i.e. below 300 MeV, only Ss for pp → ppπ 0 , [1][2][3] or at most two partial waves (Ss and Sp) for pp → dπ + and pp → pnπ + [4][5][6][7][8][9][10] were important, and direct comparisons with simple theoretical approaches can be made. The expected dominance of Ss contributions (l N N = 0, L π = 0) for the final states was seen, but at the same time it was found that for pp → ppπ 0 traditional models under-predicted the cross sections by factors of 3-5.…”
Section: Introductionmentioning
confidence: 99%